2012
DOI: 10.1111/j.1479-828x.2012.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Single incision laparoscopic surgery (SILS) in gynaecology: Feasibility and operative outcomes

Abstract: Our experience shows that SILS is a feasible and safe technique for the surgical management of various gynaecological conditions. Satisfaction is high because of improved cosmesis and reduced analgesic requirements post-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 10 publications
1
22
0
2
Order By: Relevance
“…In a study comparing single-port surgery and multiport surgery, Behnia-Willison et al reported that the single-port surgery improved cosmesis and reduced analgesic requirements [3], however others [4,8] have reported opposite results. In this study, the authors did not conduct a scientific investigation of the cosmetic outcome and recovery profile such as post-operative pain score and cost, further study might discover these questions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study comparing single-port surgery and multiport surgery, Behnia-Willison et al reported that the single-port surgery improved cosmesis and reduced analgesic requirements [3], however others [4,8] have reported opposite results. In this study, the authors did not conduct a scientific investigation of the cosmetic outcome and recovery profile such as post-operative pain score and cost, further study might discover these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, even more, a single port approach for malignant disease is upcoming and discussed all on the boil [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SATOSHI SUZUKI 1) , SHIGENORI FURUKAWA 1) , MIKI OHARA 1) , KIYOSHI KANNO 2) , SHUN YASUDA 1) , TAKEHARU OHZEKI 3) , TAKAFUMI WATANABE 1) , HIDENORI TAKAHASHI 4) , HIROSHI SUZUKI 2) and KEIYA FUJIMORI…”
Section: [Original Article] Efficacy Of 2 -Port Laparoscopic Surgery unclassified